Health selection among metal workers. - Koskela, Riitta-Sisko; Jarvinen, E; Korhonen, H; Mutanen, Pertti (Scandinavian Journal of Work, Environment & Health, 1983)
The objective of the present study was to determine which age and exposure categories are the most prone to health selection. Mortality and morbidity were studied on three different exposure levels, defined primarily according to the physical demands of the work: heavy level (iron foundries), medium level (manufacture of metal products), and light level (manufacture of electrical devices). The population comprised about 15,700 men employed in 1950--1976 in the three branches of the metal industry. The number of person-years of follow-up was about 215, 800. During the period 1950--1978, 1,407 deaths occurred. Occupational history, morbidity, and turnover causes were studied by means of a questionnaire sent to 3,500 current and former workers. The survival curves showed no great differences between the three exposure levels. However the heavy level had the highest degree of mortality, and the medium level the lowest. Foundry workers had the highest overall rates of disability. But, in the older age groups, the disability rates of the metal product workers were the highest. Less social selection was suggested for foundry workers than for the two other cohorts. Metal product workers seemed to be selected by both social and health factors. Young electrical workers were occupationally trained. On the other hand older workers with poor health were selected to this light level (negative health selection).